The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ph15111326
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Fluorescent Probe for Detection of Sulfite

Abstract: Sulfite is widely used as an antioxidant additive and preservative in food and beverages. Abnormal levels of sulfite in the body is related to a variety of diseases. There are strict rules for sulfite intake. Therefore, to monitor the sulfite level in physiological and pathological events, there is in urgent need to develop a rapid, accurate, sensitive, and non−invasive approach, which can also be of great significance for the improvement of the corresponding clinical diagnosis. With the development of fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 106 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…[19][20][21][22] Till now, several colorimetric and uorescent probes for the detection of the SO 2 derivatives (HSO 3 − /SO 3 2− ) have been designed and developed based on different sensing mechanisms such as the selective deprotection of levulinate group, [23][24][25] complexation with amines, 26,27 the selective reaction with aldehyde, 28,29 coordination to metal ions, 30 and Michael-type additions. 31,32 Among these different approaches 1,4-Michael addition of nucleophiles to a, b unsaturated systems that contain ester, ketone, nitrile, and nitro groups is one of the most versatile methods 33,34 for the development of chemosensors for the detection of SO 2 derivatives because this method allows the reaction to proceed under mild conditions. [35][36][37][38][39] Interestingly, Zhang et al (2013) 38 reported promising studies in this area, using a cationic cetyltrimethylammonium bromide (CTAB) micelle, to create a hydrophobic and basic microenvironment that promotes the addition reaction of sulte to an activated olen in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Till now, several colorimetric and uorescent probes for the detection of the SO 2 derivatives (HSO 3 − /SO 3 2− ) have been designed and developed based on different sensing mechanisms such as the selective deprotection of levulinate group, [23][24][25] complexation with amines, 26,27 the selective reaction with aldehyde, 28,29 coordination to metal ions, 30 and Michael-type additions. 31,32 Among these different approaches 1,4-Michael addition of nucleophiles to a, b unsaturated systems that contain ester, ketone, nitrile, and nitro groups is one of the most versatile methods 33,34 for the development of chemosensors for the detection of SO 2 derivatives because this method allows the reaction to proceed under mild conditions. [35][36][37][38][39] Interestingly, Zhang et al (2013) 38 reported promising studies in this area, using a cationic cetyltrimethylammonium bromide (CTAB) micelle, to create a hydrophobic and basic microenvironment that promotes the addition reaction of sulte to an activated olen in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of a sensitive fluorescence probe to study the relationship between SO 2 and drug-induced AKI is of great significance. Although many fluorescent probes have been reported to detect SO 2 in living systems, no probe has been reported to detect SO 2 in drug-induced AKI.…”
mentioning
confidence: 99%